2014
DOI: 10.1080/13540602.2014.885707
|View full text |Cite
|
Sign up to set email alerts
|

New professionalism in austere times: the employment experiences of early career teachers in Scotland

Abstract: International concern to raise educational standards and improve teacher quality has directed attention to the need to sustain career-long professional learning. Teacher induction and early professional learning (during years 2-6) have been associated with patterns of attrition and improved pupil outcomes. As the economic crisis impacts on public sector employment, the rhetoric of professionalism stands in contrast to the employment experiences of many recently qualified teachers. This article draws on intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Middle and senior leaders were viewed as strategic in allowing ECTs spaces to act, such that ECTs were able to enjoy formal and informal opportunities to take on leadership responsibilities, and the space and flexibility to take the initiative and try out new ideas. This is consonant with the findings of Hulme and Menter (2014), who report that 'positive expressions of professional growth were associated with … having the confidence and licence to experiment and "take risks''' (p. 681). This did not mean ECTs were left unsupported: leaders were available and supportive in response to ECTs' needs, but did not micro-manage them in ways that stifled their autonomy.…”
Section: Enabling Contexts and Professional Agencysupporting
confidence: 84%
See 1 more Smart Citation
“…Middle and senior leaders were viewed as strategic in allowing ECTs spaces to act, such that ECTs were able to enjoy formal and informal opportunities to take on leadership responsibilities, and the space and flexibility to take the initiative and try out new ideas. This is consonant with the findings of Hulme and Menter (2014), who report that 'positive expressions of professional growth were associated with … having the confidence and licence to experiment and "take risks''' (p. 681). This did not mean ECTs were left unsupported: leaders were available and supportive in response to ECTs' needs, but did not micro-manage them in ways that stifled their autonomy.…”
Section: Enabling Contexts and Professional Agencysupporting
confidence: 84%
“…All teachers bring to the workplace their own prior experience, knowledge and expectations, which 'intersect with the specific school context to create unique experiences, needs, and career decisions' (Ado 2013, 149). Timely institutional responsiveness to individuals' particular needs is important: ECTs in Hulme and Menter's (2014) study, for example, reported that they valued 'school-level in situ support that addressed emergent needs' (p. 677). Professional relationships based on trust (Gardiner 2012) provide the foundation on which can be built structured approaches to developing ECTs' professional learning, for example, through mentoring, 'aligned with new teachers' needs and context' (Gardiner 2012, 195), and scaffolded in ways that 'respond to immediate needs… and work towards long-term instructional goals' (ibid).…”
Section: Background and Rationale For The Studymentioning
confidence: 99%
“…Particular use is made of Mitchell Dean's (2010) analytics of government and Ball et al's (2012) work on policy enactment, to conceptualise how PP shapes the practices and 'thought' of policy subjects as they go about the everyday work of interpreting, translating and transacting the demands of the policy. Evidence is also provided that PP has ushered in insecure labour conditions for practitioners working on temporary contracts within this school, a theme that is being discussed recently in other schooling contexts (Hulme and Menter 2014) and more generally in many UK employment sectors (O'Connor 2016). Most significantly though, PP prompted staff to reconsider the concept of disadvantage in relation to their school population.…”
Section: Introductionmentioning
confidence: 99%
“…Israel (Orland-Barack & Maskit, 2011), Netherlands (Pillen, Beijaard, & den Brok, 2013), United States (Shoffner, 2011) and North of England (Kyriacou & Kunc, 2007). Research has also indicated the fragmented and casual employment experiences of beginning teachers (Hulme & Menter, 2014). The issue of beginning teachers leaving the profession in the first few years of their career has been considered as a global problem (Burke et al, 2013;Craig, 2014;Harfitt, 2015).…”
Section: Introductionmentioning
confidence: 99%